Role of Leadership in Educational Institutional Management in India - Sivalingam, Gayathiri (Global journal of Business and Integral Security, 2025)
This empirical study explores the influence of educational leadership on student growth within the Indian educational system, analyzing feedback from key stakeholders including students, teachers, and principals. A total of 510 participants were selected, comprising 250 students, 250 teachers, and 10 principals from various institutions across India. Data from students and teachers were collected through a structured 15-question survey designed to assess leadership effectiveness, communication practices, and the impact on educational outcomes. For principals, in-depth interviews using a schedule method provided deeper insights into the strategic aspects of leadership. The study aimed to evaluate how leadership practices affect different aspects of institutional efficiency and student success. By integrating the perspectives of students, teachers, and principals, the research offers a comprehensive analysis of the role of educational leaders in shaping the academic and developmental trajectories of students. Students’ responses highlighted the impact of leadership on their academic progress, while teachers emphasized the relationship between leadership and their professional development and classroom dynamics. Principals provided a strategic overview of the challenges they face in fostering a conducive learning environment. Data analysis focused on identifying common themes and discrepancies among the different stakeholder groups. Reliability tests, such as Cronbach’s Alpha (with results of 0.76 for teachers and 0.71 for students), affirmed the reliability of the survey instruments. Additional statistical tests, including ANOVA, were employed to evaluate differences in stakeholder expectations. The study’s findings are expected to inform policymakers and educational leaders, offering actionable recommendations to improve leadership practices and educational outcomes. Ultimately, this research provides valuable insights into the collective role of educational leadership and stakeholder collaboration in enhancing the Indian education system. KEYWORDS Educational leadership, Student growth, Indian educational system, Stakeholders, Leadership effectiveness, Institutional efficiency, Student success, Data analysis, Cronbach’s Alpha, Stakeholder collaboration